Efficiency of Polymer Electrolyte Membrane Fuel Cell Stack - Agung Prayitno; Olive Kubumwe; Hans Bosma; Edwin Tazelaar (Universitas Ahmad Dahlan, 2011)
This paper applies a feedforward control of optimal oxygen excess ratio that maximize net power (improve efficiency) of a NedStack P8.0-64 PEM fuel cell stack (FCS) system. Net powers profile as a function of oxygen excess ratio for some points of operation are analyzed by using FCS model. The relationships between stack current and the corresponding control input voltage that gives an optimal oxygen excess ratio are used to design a feedforward control scheme. The results of this scheme are compared to the results of a feedforward control using a constant oxygen excess ratio. Simulation results show that optimal oxygen excess ratio improves fuel cell performance compared to the results of constant oxygen excess ratio. The same procedures are performed experimentally for the FCS system. The behaviour of the net power of the fuel cell stack with respect to the variation of oxygen excess ratio is analyzed to obtain optimal values. Data of stack current and the corresponding voltage input to the compressor that gives optimal values of oxygen excess ratio are used to develop a feedforward control. Feedforward control based on constant and optimal oxygen excess ratio control, are implemented in the NedStack P8.0-64 PEM fuel cell stack system by using LabVIEW. Implementation results shows that optimal oxygen excess ratio control improves the fuel cell performance compared to the constant oxygen excess ratio control.